Nitrogen Isotope Fractionation During Archaeal Ammonia Oxidation: Coupled Estimates From Measurements of Residual Ammonium and Accumulated Nitrite - Mooshammer, Maria; Alves, Ricardo J. E.; Bayer, Barbara; Melcher, Michael; Stieglmeier, Michaela; Jochum, Lara; Rittmann, Simon K.-M. R.; Watzka, Margarete; Schleper, Christa; Herndl, Gerhard J.; Wanek, Wolfgang (Frontiers in Microbiology, 2020)
The naturally occurring nitrogen (N) isotopes, 15N and 14N, exhibit different reaction rates during many microbial N transformation processes, which results in N isotope fractionation. Such isotope effects are critical parameters for interpreting natural stable isotope abundances as proxies for biological process rates in the environment across scales. The kinetic isotope effect of ammonia oxidation (AO) to nitrite (NO2–), performed by ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB), is generally ascribed to the enzyme ammonia monooxygenase (AMO), which catalyzes the first step in this process. However, the kinetic isotope effect of AMO, or εAMO, has been typically determined based on isotope kinetics during product formation (cumulative product, NO2–) alone, which may have overestimated εAMO due to possible accumulation of chemical intermediates and alternative sinks of ammonia/ammonium (NH3/NH4+). Here, we analyzed 15N isotope fractionation during archaeal ammonia oxidation based on both isotopic changes in residual substrate (RS, NH4+) and cumulative product (CP, NO2–) pools in pure cultures of the soil strain Nitrososphaera viennensis EN76 and in highly enriched cultures of the marine strain Nitrosopumilus adriaticus NF5, under non-limiting substrate conditions. We obtained εAMO values of 31.9–33.1‰ for both strains based on RS (δ15NH4+) and showed that estimates based on CP (δ15NO2–) give larger isotope fractionation factors by 6–8‰. Complementary analyses showed that, at the end of the growth period, microbial biomass was 15N-enriched (10.1‰), whereas nitrous oxide (N2O) was highly 15N depleted (−38.1‰) relative to the initial substrate. Although we did not determine the isotope effect of NH4+ assimilation (biomass formation) and N2O production by AOA, our results nevertheless show that the discrepancy between εAMO estimates based on RS and CP might have derived from the incorporation of 15N-enriched residual NH4+ after AMO reaction into microbial biomass and that N2O production did not affect isotope fractionation estimates significantly.